Palliative Care In Hospital: Perceptions of Care : A thesis presented in partial fulfilment of the requirements for a Master of Science in Psychology at Massey University, Manawatu Campus, New Zealand - Waghorn, Sarah (Massey University, 2016)
In New Zealand, as in many other developed countries, a large number of people die in a hospital setting (Broad, Gott & Boyd, 2013). Based on New Zealand’s growing and aging population, this number is expected to increase (Ministry of Health, 2001). Previous studies have investigated how family members perceive palliative care, but there is still a lack of understanding of how families perceive this care in hospital and in particular in a New Zealand context. This research investigated how family members experienced a patient’s palliative care in a medical ward in a New Zealand hospital. Seven participants who were next-of-kin/contact person for an individual who had passed away while on a medical ward in a New Zealand hospital three to 12 months prior took part in semi-structured interviews which were analysed using thematic analysis. As a result of the analysis, five themes were identified: Physical environment, interactions with staff, communication regarding palliative care, identifying and accepting death, and care after death. These results have implications for the way in which palliative care is provided in New Zealand hospitals. Through the consideration of these factors, the experience of next-of-kin/contact people can be improved.